2008
DOI: 10.1002/mrm.21536
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically constrained reconstruction from noisy data

Abstract: Noise is a major concern in many important imaging applications. To improve data signal-to-noise ratio (SNR), experiments often focus on collecting low-frequency k -space data. This article proposes a new scheme to enable extended k -space sampling in these contexts. It is shown that the degradation in SNR associated with extended sampling can be effectively mitigated by using statistical modeling in concert with anatomical prior information. The method represents a significant departure from most existing ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 40 publications
2
128
0
Order By: Relevance
“…Many choices can be made for Ψ 1,2 (·) to incorporate prior information about the unknown spatiospectral/spatiotemporal function (e.g., those in (19,23)). In this work, we choose the following regularization form for the metabolite signal component [8] where D is a finite difference operator, W contains edge weights derived from highresolution anatomical images (17) and Ψ denotes a temporal sparsifying transform (e.g., the Fourier transform for MRSI (24)). This choice is motivated by the advantages of such edgepreserving (or non-quadratic) penalties shown in recent developments for sparse sampling and denoising.…”
Section: Image Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many choices can be made for Ψ 1,2 (·) to incorporate prior information about the unknown spatiospectral/spatiotemporal function (e.g., those in (19,23)). In this work, we choose the following regularization form for the metabolite signal component [8] where D is a finite difference operator, W contains edge weights derived from highresolution anatomical images (17) and Ψ denotes a temporal sparsifying transform (e.g., the Fourier transform for MRSI (24)). This choice is motivated by the advantages of such edgepreserving (or non-quadratic) penalties shown in recent developments for sparse sampling and denoising.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Significant efforts have been made in the last several decades to achieve fast, high-resolution MR spectroscopic imaging (MRSI), through the development of fast sequences (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and advanced image reconstruction methods (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). SPICE (SPectroscopic Imaging by exploiting spatiospectral CorrElation) is a relatively new approach that we recently proposed to achieve high-resolution MRSI with good signal-to-noise ratio (SNR) and speed (26).…”
Section: Introductionmentioning
confidence: 99%
“…For example, iterative Krylov subspace solvers like the conjugate gradient (CG) method can be used. Stone et al (2008) made a GPU implementation of a CG algorithm to enable practical use of the anatomically constrained reconstruction algorithm presented by Haldar et al (2008). Two years later, this work was extended to include correction for field inhomogeneities (Zhuo et al, 2010b), multi-GPU support (Zhuo et al, 2010c) and a regularization term for spatial smoothness (Zhuo et al, 2010a).…”
Section: Mrimentioning
confidence: 99%
“…19 F imaging with MRI offers the possibility to incorporate anatomical knowledge of the problem derived from standard proton images acquired concurrently with fluorine images. For examples from closely related fields, Haldar et al [50] incorporated anatomical information into constrained reconstructions of low-SNR MR diffusion data, and Dewaraja et al [51] showed that incorporating boundary information from CT images into iterative SPECT reconstructions can improve the resultant images.…”
Section: Model-based Medical Imaging Reconstructionmentioning
confidence: 99%
“…anatomical data provided by CT [51,[83][84][85]. Furthermore, there are MRI analogies to the class of super-resolution-through-image-denoising methods [50] and to techniques that have been used to jointly estimate images obtained with differing contrasts [86]. Since there should be a high correlation between where we observe fluorine signal and organ and tissue boundaries in the body, many of these ideas are directly applicable to the secondary nucleus situation.…”
Section: Introductionmentioning
confidence: 99%